Perencanaan Sistem Pewadahan dan Pengumpulan Sampah Rumah Tangga di Bantaran Sungai Cikapundung Kota Bandung - Muhamad Yogi Arsyandi; Yulianti Pratama; Lina Apriyanti (Fakultas Teknik, 2019)
The increase of population in an area will have an impact on the level of density of the area, so that the emergence of a wild settlement that utilizes the river area as a place of residence. This condition will be a potential waste problem in the Riverbank area. One of them is the potential for garbage dumped into rivers, especially Cikapundung River. Tamansari Village is one of the areas that are traversed Cikapundung river, so it takes the planning of the system of inheritance and garbage collection to reduce the potential of waste dumped into the river. waste generation measurement based on SNI 19-3964-1994 method. The concept of waste management system planning is the reduction of waste in the source by 30% with the planning of the timing system through sorting based on three categories of garbage types. Planning of collecting system is by giving the gathering to the collecting device compartment. A community-based waste processing approach that starts from sourcing through composter processing and garbage bank.